2015
DOI: 10.1016/j.proenv.2015.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Natural Ventilation and Temperature Conditions in Some High-rise Building Flats in Bandung and Jakarta in Perspective of Adaptive Thermal Comfort

Abstract: The effect of increasing RUSUNAMI high-rise and low cost building flats construction has brought about some problems. One of them is the use of air conditioning in many building flats. It shows that the objective of the RUSUNAMI is not fulfilled because it needs additional operational cost for air conditioning. Two RUSUNAMIs in Bandung and three RUSUNAMIs in Jakarta were selected and measured related to ventilation and indoor air temperature. This paper examines the performance of natural ventilation and indoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…In order to offset the discomfort in a warm-humid environment, higher air velocity should be introduced, and this can range, as the study shows, between 0.2-0.6 m/s. The condition is difficult to be attained in a standard building design as the average air velocity generally does not exceed 0.2 m/s (Aflaki et al, 2016;Alfata et al, 2015;Sujatmiko et al, 2015). Nevertheless, previous studies indicated several strategies could be employed to meet the objective.…”
Section: Contribution Of the Strategy To Comfortmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to offset the discomfort in a warm-humid environment, higher air velocity should be introduced, and this can range, as the study shows, between 0.2-0.6 m/s. The condition is difficult to be attained in a standard building design as the average air velocity generally does not exceed 0.2 m/s (Aflaki et al, 2016;Alfata et al, 2015;Sujatmiko et al, 2015). Nevertheless, previous studies indicated several strategies could be employed to meet the objective.…”
Section: Contribution Of the Strategy To Comfortmentioning
confidence: 99%
“…Nevertheless, previous studies indicated several strategies could be employed to meet the objective. For example, the correct window orientation relative to wind direction may increase air velocity up to 0.4 m/s (Sujatmiko et al, 2015). Wing walls or fins can also be incorporated into the design and elevate the air velocity 0,3 m/s above the standard design (Mozaffari Ghadikolaei et al, 2020).…”
Section: Contribution Of the Strategy To Comfortmentioning
confidence: 99%
“…The solution for this problem is traditionally associated with special engineering facilities [23,24], which make construction more expensive and, therefore, restricts the amount of potential buyers. Similar contradictions arise when designing ventilation and air conditioning systems in high-rise buildings [25,26]. In Russia, the introduction of sustainable technologies is in a formative stage.…”
Section: International Practices and Russian Prospects For The Designmentioning
confidence: 91%
“…Beberapa bangunan yang mempunyai bukaan pada sisi timur dan barat yang mempunyai intensitas panas matahari yang tinggi sangat perlu untuk menambahkan elemen design pada sisi yang menghadap matahari untuk dapat mengurangi intensitas panas yang masuk, dengan tetap mendapatkan cahaya atau udara yang diinginkan. Penerapan selubung bangunan yang tidak tepat akan mendorong penggunaan pendingin ruangan, yang akhirnya akan meningkat kebutuhan energi suatu bangunan [8], [14].…”
Section: Peran Selubung Bangunanunclassified